2019
DOI: 10.1177/2042018819863022
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine in adult and pediatric obesity: a clinical perspective

Abstract: It remains largely unknown as to why some individuals experience substantial weight loss with obesity interventions, while others receiving these same interventions do not. Person-specific characteristics likely play a significant role in this heterogeneity in treatment response. The practice of precision medicine accounts for an individual’s genes, environment, and lifestyle when deciding upon treatment type and intensity in order to optimize benefit and minimize risk. In this review, we first discuss biopsyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 145 publications
(250 reference statements)
1
47
0
Order By: Relevance
“…Furthermore, commercial meal replacement programs can be expensive, with some analyses suggesting they are prohibitively cost ineffective [13]. Drug treatments are available [14], but as with lifestyle interventions, there is heterogeneity both in how much weight is lost and the improvements seen in glycemic control with different medications [15]. Bariatric surgery is efficacious and cost effective [16], particularly in patients with type 2 diabetes, where sustained remission is feasible for a substantial proportion of patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, commercial meal replacement programs can be expensive, with some analyses suggesting they are prohibitively cost ineffective [13]. Drug treatments are available [14], but as with lifestyle interventions, there is heterogeneity both in how much weight is lost and the improvements seen in glycemic control with different medications [15]. Bariatric surgery is efficacious and cost effective [16], particularly in patients with type 2 diabetes, where sustained remission is feasible for a substantial proportion of patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…A recently published international consensus statement about the stigma of obesity addressed the impact of unproven assumptions that attribute body weight to a lack of self-discipline and personal responsibility (Rubino et al, 2020). Weight stigma, discrimination, and bullying can lead to maladaptive eating which increases risk for unhealthy weight in susceptible children ( Bomberg et al, 2019 ; Puhl, Himmelstein, & Pearl, 2020 ). Weight-based teasing, whether in person or in cyber space, can lead to further weight gain as a response to stress ( Schvey et al, 2019 ).…”
mentioning
confidence: 99%
“…33 This includes an increased interest in the use of precision medicine, also known as personalized medicine, for the prevention and treatment in those with overweight and obesity, an approach that incorporates individual variability in the genes, environment, and lifestyle for each individual. [34][35][36] The assumption of precision medicine is that true inter-individual differences exist, for example, responders and nonresponders, to an intervention. While it has been suggested that inter-individual variability exists with respect to exercise-associated changes in adiposity among children, adolescents, and adults, [37][38][39][40][41][42][43] the focus of these studies has been on group mean data with little regard to inter-individual variation in which differences in change outcome standard deviations between both the exercise and control groups are examined.…”
Section: Introductionmentioning
confidence: 99%